Helping Babies Breathe (HBB) Program for Reduction of Neonatal Mortality: A Hospital Based Cost Effective Intervention in Nepal - Thapa, Kanchan; Clark, Robert B.; Visick, Michael K.; Basaula, Yubanidhi; Hamal, Rakesh; KC, Naresh Pratap (Medical Journal of Shree Birendra Hospital, 2020)
Helping Babies Breath (HBB) is an evidence based educational curriculum practiced worldwide to teach neonatal resuscitation. It is famous and cost effective intervention in resource limited setting. In this regard, we have been implementing HBB program in Nepal through hospitals where delivery rate is higher. In this program, a pair of trainers have been trained as Master Trainer. These trainer back to hospital and train their colleagues in own facility. We have already produced more than seven hundred master trainers from hospital, nursing college, medical colleges and university in Nepal. Through the program, it aims to reduce the neonatal morbidity and mortality so that the country will achieve the target set by SDGs.